A importância do estudo dos egressos de pedagogia pela educação ambiental na educação infantil - Bezerra, Liliane Alves (Universidade Federal do Tocantins, 2022)
This article aims to map the academic interest of pedagogy graduates from the Federal University of Tocantins (UFT) on the theme of environmental education in basic education, with emphasis on the early childhood education stage. To carry out this research, it was necessary to use the methodology of documentary research, of a qualitative nature, regarding the Course Completion Works (TCC's) built by the graduates of the Pedagogy course of that institution. For that, the four university campuses that have the Pedagogy course were contemplated as the focus of our research, they are: Arraias, Miracema, Palmas and Tocantinópolis. The results indicate that only three works available in the UFT digital collection by graduates of the aforementioned course address the theme of Environmental Education, although none of them directly dialogue with the Early Childhood Education stage. It is concluded, therefore, that the study of this theme should be further encouraged in the process of initial training.